When Meaning Collapses: Nihilism, Violent Extremism, and the Promise of Logotherapy - Zora Arfina Sukabdi (Asosiasi Psikologi Forensik (Apsifor), 2026)
Contemporary violent extremism among youth is increasingly defined by existential vulnerability as well as ideological commitment. Recent cases in Indonesia involving adolescents exposed to extremist content via digital platforms indicate a shift away from traditional forms of terrorism based on organized recruitment, religious indoctrination, and political grievances and toward more fragmented forms of radicalization shaped by